Changes in Koppen–Trewartha climate classification over South America from RegCM4 projections. (19th October 2017) - Fernandez, Julio P. R.; Franchito, Sergio H.; Rao, V. Brahmananda; Llopart, Marta
Abstract: The Koppen–Trewartha (K–T) classification is used to investigate the biomes change in the future climate over South America (SA). For the middle (2035–2060) and end (2075–2100) of the 21st century mean ensemble of Regional Climate Model version 4 simulations for the Representative Concentration Pathway 8.5 scenario are presented. The global‐coupled models of Coupled Model Intercomparison Project Phase 5 drive the members for the period 1970–2100 using different physics configurations. The delta change approach is applied to filter out the bias of the model simulation. Notable changes of the K–T climates are found in SA, mainly in Brazil. Replacement of tropical wet‐dry (Aw) by dry semiarid (Bs) occurs over Northeast Brazil (NEB). Reduction of tropical humid (Ar) and an increase of Aw is projected in the North Brazil and Amazon. Retreat of subtropical humid (Cr) replaced by Aw is found in the Southeast Brazil. An increase of subtropical winter‐dry (Cw) and decrease Cr is noted in Argentina and in Paraguay Cr is replaced by Ar. In the south of SA, a retreat of subarctic oceanic (Eo) and an increase of temperate oceanic (Do) and dry arid (Bw) occur. In general, the projected changes of K–T climate types in the 21st century over SA show a tendency for a drier climate. Abstract : Model domain. Shown are the topography (m) and regions of SA: NSA: North of South America, 5°–12°N, 77°–58°W; AMZ: Amazon, 10°S–5°N, 75°–55°W; NAR: North of Argentina, 39°–23°N, 68°–58°W; SSA: South of South America, 55°–39°S, 75°–62°W; AND: Andes 2000 m above msl, and over Brazil: NO: north, 10°S–1°N, 69°–45°W; CW: center‐west, 23°–10°S, 62°–50°W; NEB: northeast, 15°–3°S, 45°–35°W; SE: southeast, 25°–15°S, 52°–40°W; and S: south, 34°–21°S, 58°–48°W.